Myanmar's enemy within : Buddhist violence and the making of a Muslim 'other' - Wade, Francis (Asian arguments., 2019)
Explores the growing divide between Myanmar's Buddhist and Muslim communities, and questions why some of the most respected and articulate voices for democracy in the country have become complicit in the persecution of its religious minorities.